No wonder, it is a hybrid. Natural hybridization between Jacobaea vulgaris and J. erucifolia revealed by molecular marker systems and its potential ecological impact - Barbara Gawrońska; Małgorzata Marszałek; Piotr Kosiński; Marek Podsiedlik; Leszek Bednorz; Joanna Zeyland (Ecology and Evolution, 2023)
Abstract Progressive changes in the environment are related to modifications of the habitat. Introducing exotic species, and interbreeding between species can lead to processes that in the case of rare species or small populations threatens their integrity. Given the declining trends of many populations due to increased hybridization, early recognition of hybrids becomes important in conservation management. Natural hybridization is prevalent in Jacobaea. There are many naturally occurring interspecific hybrids in this genus, including those between Jacobaea vulgaris and its relatives. Although Jacobaea erucifolia and J. vulgaris often co‐occur and are considered closely related, apart from the few reports of German botanists on the existence of such hybrids, there is no information on research confirming hybridization between them. Morphologically intermediate individuals, found in the sympatric distributions of J. vulgaris and J. erucifolia, were hypothesized to be their hybrids. Two molecular marker systems (nuclear and chloroplast DNA markers) were employed to test this hypothesis and characterize putative hybrids. Nuclear and chloroplast DNA sequencing results and taxon‐specific amplified fragment length polymorphism (AFLP) fragment distribution analysis confirmed the hybrid nature of all 25 putative hybrids. The AFLP patterns of most hybrids demonstrated a closer relationship to J. erucifolia, suggesting frequent backcrossing. Moreover, they showed that several individuals previously described as pure were probably also of hybrid origin, backcrosses to J. erucifolia and J. vulgaris. This study provides the first molecular confirmation that natural hybrids between J. vulgaris and J. erucifolia occur in Poland. Hybridization appeared to be bidirectional but asymmetrical with J. vulgaris as the usual maternal parent.